Precise positioning and identification card for mine vehicles based on domestic chip - Jianbo DAI (Meikuang Anquan)
Aiming at the problem that high power consumption of designed identification card with imported chip leads to frequent battery charging, frequent replacement and difficult maintenance, which is not suitable for the long-term position tracking of various vehicles in the coal mine, a precise positioning identification card based on the domestic chip for mine vehicles is designed. This paper introduces the design of hardware and software to reduce the power consumption of the identification card. The hardware adopts the domestic chip design; the software optimizes the positioning network algorithm and adaptively adjusts the RF transmission power. The test results show that the combination of hardware and software ensures constant positioning accuracy, improves communication distance, reduces product costs, extends the service life of the identification card, and improves the efficiency and turnover rate of underground auxiliary transportation of the vehicles.